Topologically controlled multiskyrmions in photonic gradient-index lenses - Shen, Yijie (2024)
Skyrmions are topologically protected quasiparticles, originally studied in condensed-matter systems and recently in photonics, with great potential in high-density information storage. Despite the recent attention, most optical solutions require complex systems yet produce limited topologies. Here we demonstrate an extended family of quasiparticles beyond normal skyrmions that are controlled in compact photonic gradient-index media, extending to higher-order members such as multiskyrmions and multimerons, with increasingly complex topologies. We introduce multiple topological numbers (centrality, radiality, vorticity, and polarity) in addition to the skyrmion number to describe these photonic quasiparticles. Our compact creation system lends itself to integrated and programmable solutions of complex particle textures, with potential impacts on both photonic and condensed-matter systems for revolutionizing topological informatics and logic devices.